Advancements in the study of acute lung injury resulting from intestinal ischemia/reperfusion - Lv, Shihua; Zhao, Xudong; Ma, Can; Zhao, Dengming; Sun, Tian; Fu, Wenchao; Wei, Yuting; Li, Wenzhi (Frontiers in Medicine, 2024)
Intestinal ischemia/reperfusion is a prevalent pathological process that can result in intestinal dysfunction, bacterial translocation, energy metabolism disturbances, and subsequent harm to distal tissues and organs via the circulatory system. Acute lung injury frequently arises as a complication of intestinal ischemia/reperfusion, exhibiting early onset and a grim prognosis. Without appropriate preventative measures and efficacious interventions, this condition may progress to acute respiratory distress syndrome and elevate mortality rates. Nonetheless, the precise mechanisms and efficacious treatments remain elusive. This paper synthesizes recent research models and pertinent injury evaluation criteria within the realm of acute lung injury induced by intestinal ischemia/reperfusion. The objective is to investigate the roles of pathophysiological mechanisms like oxidative stress, inflammatory response, apoptosis, ferroptosis, and pyroptosis; and to assess the strengths and limitations of current therapeutic approaches for acute lung injury stemming from intestinal ischemia/reperfusion. The goal is to elucidate potential targets for enhancing recovery rates, identify suitable treatment modalities, and offer insights for translating fundamental research into clinical applications.